持続血液濾過透析により改善したメトホルミンによる乳酸アシドーシスの1例(A case of intractable lactic acidosis associated with Metformin overdose). Issue 2 (18th February 2021) - (Youhei Nakamura), 中村 洋平; (Hiroshi Ogura), 小倉 裕司; (Hiroko Matsui), 松井 浩子; (Shinichiro Maeda), 前田 真一郎; (Takeshi Shimazu), 嶋津 岳士
ABSTRACT: An 81–year–old man with diabetes and chronic heart failure presented with a 3–week history of loss of appetite. He was transported to the emergency department due to disturbance of consciousness and shock. Vital signs included: body temperature, 32.1℃; blood pressure, 68/24mmHg; respiratory rate, 16 breaths/min; heart rate, 24 beats/min; and Glasgow coma scale, E2V1M4. Arterial blood gas analysis showed lactic acidosis and hyperkalemia. He was underwent coronary angiography (CAG), and a temporary pacing catheter was inserted. Concurrently, fluid resuscitation, administration of catecholamine and continuous hemodiafiltration (CHDF) were started. CAG showed normal coronary arteries. However, 4h after admission, lactic acidosis had not improved. We therefore performed exploratory laparotomy to rule out mesenteric ischemia. No intestinal ischemia was identified. Six hours after admission, lactic acidosis showed gradual improvement. In this case, metformin concentration in blood was 48.6µg/mL on admission and 18.8µg/mL at 14h after the start of CHDF. We diagnosed metformin–associated lactic acidosis (MALA). The patient showed steady improvement and CHDF was finished on day 6. On day 9, he was discharged without any complications. In this report, we suggest the effectiveness of CHDF for MALA. 要旨: 糖尿病性腎症，慢性心不全を加療中の81歳の男性。3週間続く食思不振後に意識障害，徐脈，ショックを呈し搬送となった。意識レベルはGCS E2V1M4，呼吸数16/min，血圧68/24mmHg，脈拍24/min，膀胱温32.1℃であった。血液ガス分析にてpH 6.941，乳酸値127mg/dL，カリウム値7.2mEq/Lと著明な乳酸アシドーシスを認めた。大量輸液，カテコラミン投与，経静脈ペーシング，持続血液濾過透析（CHDF）を開始した。冠動脈造影検査で急性期異常なく，腸管虚血，敗血症性ショック，メトホルミンによる乳酸アシドーシス（MALA）を念頭に治療を継続した。CHDF開始4時間後で乳酸値145mg/dLと改善なく，腹部膨満と腹水貯留が増悪し，試験開腹術を施行したが，腸管壊死は認めなかった。全身管理を継続し，CHDF開始6時間後より乳酸値は113mg/dLと改善を認め，入院3日目に正常化した。後日判明した血中メトホルミン濃度は，搬送時48.6μg/mLと高値を示し，CHDF開始14時間後に18.8μg/mLと改善しており，MALAと診断した。入院6日目にCHDFを離脱し，9日目にリハビリ転院となった。重篤なMALAに対するCHDFは，血中メトホルミン濃度の低下と乳酸アシドーシス改善に有効と考えられた。